PTSD treatment in times of COVID-19: A systematic review of the effects of online EMDR - Lenferink, L.I.M.; Meyerbröker, K.; Boelen, P.A. (Psychiatry research, 2020)
•Meta-analyses showed that the effects of online CBT for PTSD are promising.•Worldwide only one trial examined the effects of online EMDR for PTSD.•Wider usage and implementation of online EMDR seems premature in times of COVID-19. COVID-19 affects many societies by measures as “social distancing”, forcing mental health care professionals to deliver treatments online or via telephone. In this context, online Eye Movement Desensitization and Reprocessing (EMDR) is an emerging treatment for patients with Posttraumatic Stress Disorder (PTSD). We performed a systematic review of studies investigating online EMDR for PTSD. Only one trial was identified. That uncontrolled open trial showed promising results. There is an urgent need to further examine the effects of online EMDR for PTSD, before its wider dissemination is warranted. Remotely delivered cognitive behavioural therapy seems the preferred PTSD-treatment in times of COVID-19.